Public Perceptions of Political Parties: A Thematic Analysis Based on Solomon's Perception Theory - Pipit Nurvina (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze public perceptions of political parties using Michael R. Solomon's perception theory framework. The low level of public trust in political parties in Indonesia is the main background of this study. Using a qualitative approach with thematic analysis methods, this study involved 10 purposively selected informants. Data were collected through in-depth interviews and analyzed through three coding stages: open coding, axial coding, and selective coding. The results identified eight main perception themes: (1) negative perceptions of political parties, (2) positive perceptions of political figures, (3) psychological burden, (4) social media as a source of information, (5) economic orientation, (6) political idealism, (7) apathy, and (8) changes in perception due to direct experience. Analysis using Solomon's perception theory shows that selective attention, selective distortion, selective retention, interpretation, perceived risk, and perceptual mapping play a significant role in shaping public perception. The majority of informants do not pay attention to political stimuli (selective attention), tend to distort positive information (selective distortion), and only remember negative information (selective retention). This study concludes that the crisis of trust in political parties is multidimensional and requires a repositioning strategy that includes increasing content salience, providing positive direct experiences, developing role models, and reducing perceived risk.